Marketing Strategy on Purchase Decisions for Toyota All New Veloz Cars - Abdul Haris (Jurnal Economic Resource, 2022)
This study aims to determine the influence of product, price, promotion, and distribution factors on purchasing decisions of the Toyota All New Veloz in Makassar City. The population in this study were all Toyota All New Veloz owners in Makassar City. The sampling technique was accidental random sampling, namely, taking a sample from every member of the target population in the field. The data in this study used primary data collected by distributing questionnaires to all respondents. The data analysis method used is descriptive statistical analysis, research instrument testing consisting of (validity test, reliability test) and testing of all hypotheses through partial tests, simultaneous tests, and tests of the coefficient of determination. The study results show that the marketing mix, which consists of product, price, promotion, and distribution, partially influences the purchasing decision of the Toyota All New Veloz Car in Makassar City. This shows that the better the product, the lower the price, the better the promotion, and the more and better the distribution can increase the interest and purchase decision of the Toyota All New Veloz Car in Makassar City. The product is the dominant factor influencing the decision to purchase the Toyota All New Veloz in Makassar City. This indicates that if the same amount increases the value of the product, price, promotion, and distribution, then the value of the consumer's purchasing decision is determined by the product.